Unusual promoters and leaving groups in glycosylation reactions: The evolution of carbohydrate synthesis. (September 2022) - Morelli, Laura; Compostella, Federica; Panza, Luigi; Imperio, Daniela
Abstract: Glycosylation is the key reaction by which our body can produce and modify carbohydrates and their conjugates which are molecules essential for life. The study of the diversity of their functions is a current and ever-expanding topic that requires the ability to provide pure saccharides quickly, efficiently and in a controlled way which can be achieved by chemical synthesis. Although the influence of the donor and the promoter on the outcome of a glycosylation reaction is well documented, the search for new methodologies and new promoters/activators is constantly expanding. In this review, after an introduction dealing with well-known glycosylation strategies, we describe the most recent advances in terms of the use of innovative approaches, focalizing the study on new promoters and leaving groups exploited in the last ten years. Graphical abstract: Image 1 Highlights: New methodologies and new reagents in glycosylation reaction. Discussion on recent promoters derived from transition metals, boron derivatives, and Halogens. Comparison of the roles of leaving groups from ethers and esters, S-derivatives and N -oxyacetamides for regioselectivity.